Laser blow-off with photodiode detection system at the helically symmetric experiment. (9th November 2021) - Castillo, J.F.; Clark, C.; Bader, A.; Likin, K.M.; Anderson, D.T.; Geiger, B.; Kumar, S.T.A.; Swee, C.
Abstract: A laser blow-off (LBO) system has been installed in the HSX stellarator to investigate impurity transport. A Nd:YAG laser is used to ablate a target area on a glass slide that has been coated with a thin film of aluminum and rapidly deposits a small, controlled quantity of aluminum atoms into HSX plasma. To study the radial propagation and confinement of the injected aluminum impurities, time-resolved emission measurements are made using a 20 channel AXUV photodiode detection system. The LBO system has achieved its design purpose, most notably the ability to make controlled impurity injection without significant perturbation to the background plasma. A detailed description of the setup as well as initial results of operation are presented.